Privatized Keynesianism or conspicuous consumption? Status anxiety and the financialization of consumption in Chile - Felipe González (Max Planck Institute for the Study of Societies, 2017)
Why do people acquire consumer debt? In this article, I draw on the case of Chile and call into question the explanatory power of both the "trickle-down" and "privatized Keynesianism" hypotheses. I argue that these narratives fail to explain why, in the context of wage improvements, consumers use credit to finance "ordinary" forms of consumption that do not aim to protect lifestyles or signal status to others, but rather reflect a subtler expansion of the standard of living. Building on the idea that consumer debt is used to fill a gap between income and a socially constructed standard of living, I show that financialization might be explained by two subtler mechanisms in the case of Chile and, arguably, other developing countries: spurious upward mobility and relative deprivation. In both cases, families consume beyond their means in order to perform their class identities and meet the consumption standards to which they feel entitled. Instead of imitating the rich, consumers seek to perform their belonging to an "imaginary middle class." – – Weshalb nehmen Verbraucher Kredite auf? Am Beispiel von Chile hinterfrage ich in diesem Beitrag die Erklärungskraft, die sowohl die Trickle-down-Theorie als auch die Theorie des privatisierten Keynesianismus bei diesem Thema entfalten. Beide Narrative erklären nicht, warum Verbraucher vor dem Hintergrund von Lohnerhöhungen Kredite nutzen, um ganz normalen Konsum zu finanzieren, der weder einen bestimmten Lebensstil absichern noch Dritten gegenüber einen bestimmten Status signalisieren soll, sondern vielmehr dazu dient, den Lebensstandard auf eher dezente Weise zu erhöhen. Ausgehend von der Vorstellung, dass private Verschuldung die Lücke zwischen Einkommen und einem sozial konstruierten Lebensstandard schließen soll, schlage ich vor, die Finanzialisierung im Fall Chiles - und wohl auch weiterer Entwicklungsländer - durch zwei nuanciertere Mechanismen zu erklären: erstens durch vorgetäuschte Aufwärtsmobilität und zweitens durch relative Deprivation. In beiden Fällen leben Familien über ihre Verhältnisse, um ihre Klassenidentitäten auszufüllen und die Konsumstandards zu befolgen, zu denen sie sich berechtigt fühlen. Durch Kreditaufnahme möchten Verbraucher nicht die Wohlhabenden imitieren, sondern vielmehr ihre Zugehörigkeit zu einer "imaginären Mittelschicht" zeigen.
hdl:11858/00-001M-0000-002C-C86C-D
Keywords: 300; trickle-down consumption effect; privatized Keynesianism; status anxiety; spurious mobility; relative deprivation; Trickle-down-Effekt; privatisierter Keynesianismus; Statusangst; Scheinaufstieg; relative Deprivation